2003
DOI: 10.1002/chin.200312034
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Asymmetric Two‐Center Catalysts in Phase‐Transfer Reactions.

Abstract: Enantioselective synthesesEnantioselective syntheses O 0031 Development of New Asymmetric Two-Center Catalysts in Phase-Transfer Reactions. -New asymmetric two-center catalysts of type (I) are designed and tested for the asymmetric phase-transfer Michael alkylation and Michael addition of the glycine derivative (II). -(SHIBUGUCHI, T.; FUKUTA, Y.; AKACHI, Y.; SEKINE, A.; OHSHIMA, T.; SHIBASAKI*, M.; Tetrahedron Lett. 43 (2002) 52, 9539-9543; Grad. Sch. Pharm. Sci., Univ. Tokyo, Bunkyo, Tokyo 113, Japan; Eng.) -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These Maruoka catalysts were found to be highly effective for a variety of asymmetric transformations (e.g., Michael additions, α-amino acid syntheses, epoxidations, aldol-type reactions, isoxazoline syntheses,..), even using only minimum amounts of catalysts (<1 mol%) [ 4 , 5 , 30 , 31 , 32 , 33 , 34 , 35 ], thus belonging to the most powerful and versatile PTCs known to date. In addition, also Shibasaki’s tartaric acid-derived bidentate PTCs [ 36 , 37 , 38 ] and Lygo’s biphenyl-based spirocyclic catalysts [ 39 , 40 ] have proven their potential in different asymmetric applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Maruoka catalysts were found to be highly effective for a variety of asymmetric transformations (e.g., Michael additions, α-amino acid syntheses, epoxidations, aldol-type reactions, isoxazoline syntheses,..), even using only minimum amounts of catalysts (<1 mol%) [ 4 , 5 , 30 , 31 , 32 , 33 , 34 , 35 ], thus belonging to the most powerful and versatile PTCs known to date. In addition, also Shibasaki’s tartaric acid-derived bidentate PTCs [ 36 , 37 , 38 ] and Lygo’s biphenyl-based spirocyclic catalysts [ 39 , 40 ] have proven their potential in different asymmetric applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the easily available natural chiral sources, tartaric acid ( 1 ) has obtained a prominent position, especially due to the fact that both enantiomers are readily available in sufficient quantities. Although Shibasaki et al have demonstrated the potential of tartaric acid-derived bidentate PTCs [ 36 , 37 , 38 ], others were less successful in their attempts to synthesize powerful tartaric acid-derived quaternary ammonium salt catalysts [ 41 , 42 ]. Based on the high potential of tartaric acid-derived easily obtainable tetraaryl-2,2-dimethyl-1,3-dioxolan-4,5-dimethanols (TADDOLs, 2 ) as chiral ligands in (transition-) metal catalysis [ 46 , 47 ] we have recently carried out systematic investigations to use this unique structural motive for the syntheses of chiral N -spiroquaternary ammonium salt catalysts [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, complexation not only through mono-interaction between each functional group in the catalyst and in the substrate, but also through multi-interaction containing additional functional group(s) in some cases is required for effective molecular recognition. Thus, a lot of intelligent molecules with multi-functions have been designed and prepared by introducing different functional, but mutually noninteractive, groups to the original molecule [2].Individual reaction in living organisms is strictly controlled by reactant-substrate specificity, as exemplified in enzymatic reactions, even though the total mode of action is systematically controlled by correlation with other reactions. Host-guest interaction in inclusion chemistry using cyclodextrin [3] is a typical example of specific reactions in an artificial field.…”
mentioning
confidence: 99%
“…Therefore, complexation not only through mono-interaction between each functional group in the catalyst and in the substrate, but also through multi-interaction containing additional functional group(s) in some cases is required for effective molecular recognition. Thus, a lot of intelligent molecules with multi-functions have been designed and prepared by introducing different functional, but mutually noninteractive, groups to the original molecule [2].…”
mentioning
confidence: 99%